Muscle disorders and dentition-related aspects in temporomandibular disorders: controversies in the most commonly used treatment modalities - Jerjes, Waseem (BioMed Central, 2008)
This review explores the aetiology of temporomandibular disorders and discusses the controversies in variable treatment modalities. Pathologies of the temporomandibular joint (TMJ) and its' associated muscles of mastication are jointly termed temporomandibular disorders (TMDs). TMDs present with a variety of symptoms which include pain in the joint and its surrounding area, jaw clicking, limited jaw opening and headaches. It is mainly reported by middle aged females who tend to recognize the symptoms more readily than males and therefore more commonly seek professional help. Several aetiological factors have been acknowledged including local trauma, bruxism, malocclusion, stress and psychiatric illnesses. The Research Diagnostic Criteria of the Temporomandibular Disorders (RDC/TMD) is advanced to other criteria as it takes into consideration the socio-psychological status of the patient. Several treatment modalities have been recommended including homecare practices, splint therapy, occlusal adjustment, analgesics and the use of psychotropic medication; as well as surgery, supplementary therapy and cognitive behavioural therapy. Although splint therapy and occlusal adjustment have been extensively used, there is no evidence to suggest that they can be curative; a number of evidence-based trials have concluded that these appliances should not be suggested as part of the routine care. Surgery, except in very rare cases, is discouraged since it is the most invasive alternative; recent studies have shown healthier outcome with cognitive behavioural therapy.